The Influence of Slow Deep Breathing Technique on Inpatient Anxiety - Nusa Harta, I Putu Arika; Kamaryati, Ni Putu; Putra, I Nyoman Arya Maha; Wicaksana, IGA Tresna (Babali Publisher, 2023)
Previous studies have shown that slow deep breathing techniques provide benefits in reducing anxiety in general, but there has been no specific review investigating its benefits in inpatient populations. Objective: To provide strong and up-to-date evidence on the effectiveness of slow deep breathing technique as a potential intervention in reducing anxiety in the inpatient population. Methods: This study is a literature review conducted during April-May 2023 using Google Scholar, PubMed, and ScienceDirect. The keywords used were